A quantitative model to fine-tune tourism as a black rhinoceros (diceros bicornis) conservation tool in North-West Namibia - Muntifering, Jeffrey Robert (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.